Metacognitive beliefs and rumination as predictors of anger: A prospective study. Issue 5 (23rd February 2017) - Caselli, Gabriele; Offredi, Alessia; Martino, Francesca; Varalli, Davide; Ruggiero, Giovanni M.; Sassaroli, Sandra; Spada, Marcantonio M.; Wells, Adrian
Abstract : The metacognitive approach conceptualizes the relationship between anger and rumination as driven by metacognitive beliefs, which are information individuals hold about their own cognition and about coping strategies that impact on it. The present study aimed to test the prospective predictive impact of metacognitive beliefs and rumination on anger in a community sample. Seventy‐six participants were recruited and engaged in a 2‐week anger, rumination, and metacognitive beliefs monitoring protocol. A multi‐wave panel design was employed to test whether metacognitive beliefs and rumination have a prospective impact on anger. Metacognitive beliefs and rumination were found to have a significant prospective impact on anger that was independent from the number of triggering events. Metacognitive beliefs about the need to control thoughts were shown to have a direct impact on subsequent anger, independently from rumination. These findings provide support for the potential value for applying metacognitive theory and therapy to anger‐related problems. Aggr. Behav. 43:421–429, 2017. © 2017 Wiley Periodicals, Inc.